(untitled) (Journal of Nonlinear Modeling and Analysis, 2024)
This paper mainly concerns with a class of nonlinear Hilfer fractional neutral recurrent neural networks with time varying delays. The existence and uniqueness of solutions in the space of weighted continuous functions are established by Banach’s contraction principle. Finally, an example is provided to illustrate the application of the obtained results.